O uso dos recursos pedagógicos mediados pelo professor no ensino dos conceitos geométricos a um educando com TEA - Almeida, Rosângela Pereira de (2019)
The present work is the presentation of a research, whose objective was, fron the perspective of Inclusive Mathematical Education, to develop mediations and teaching strategies of geometric concepts defined by the Common National Curriculum Base (BNCC) for the 2nd Year of Elementary School in the class in participating a student whit Autistic Spectrum Disorder (ASD). In field work at school, we planned teaching resources that were applied to the students, contemplating, during the operationalization period of our intervention project, the student ASD duly enrolled in the regular school. This research aims to verify what mediations and pedagogical resources the teacher can use in teaching geometry to students with Autism Spectrum Disorder (ASD) in literacy phase. We use Vygotsky's (1994), (1995), (1997), Historical-Cultural Theory, especially the concept of mediation, as one of the theoretical assumptions that support the investigation research and pedagogical actions based on Inclusive Education (MANTOAN, 1997a, 1997b). The research used, participant observation, instruments and techniques, field diary, semi-structured interview, audio recording with the student's mother with ASD and the conducting and supportive teachers in order to know the characteristics of the student with ASD and the teacher. context in which it fits. We plan the actions to be taken in order to fulfill the proposal. The pedagogical instruments (dynamics, elaborate tasks and manipulable materials) used were fundamental in the reach of the students of that classroom, whose main focus was the student with ASD. Through the application of these resources, it was possible to understand from the data analysis, how the mediations proposed by the teacher can provide significant advances in the knowledge of the concepts to these students. Finally, we built a pedagogical proposal as an educational product, containing the actions performed during the intervention, in order to contribute to teachers of Inclusive Mathematical Education to posterity.